The Grain Boundary Wetting Phenomena in the Ti‐Containing High‐Entropy Alloys: A Review - Straumal, Boris B.; Korneva, Anna; Kuzmin, Alexei; Lopez, Gabriel A.; Rabkin, Eugen; Straumal, Alexander B.; Gerstein, Gregory; Gornakova, Alena S. (MDPI, 2021)
In this review, the phenomenon of grain boundary (GB) wetting by melt is analyzed for multicomponent alloys without principal components (also called high-entropy alloys or HEAs) containing titanium. GB wetting can be complete or partial. In the former case, the liquid phase forms the continuous layers between solid grains and completely separates them. In the latter case of partial GB wetting, the melt forms the chain of droplets in GBs, with certain non-zero contact angles. The GB wetting phenomenon can be observed in HEAs produced by all solidification-based technologies. GB leads to the appearance of novel GB tie lines Twmin and Twmax in the multicomponent HEA phase diagrams. The so-called grain-boundary engineering of HEAs permits the use of GB wetting to improve the HEAs’ properties or, alternatively, its exclusion if the GB layers of a second phase are detrimental.--/-- This review is published under CC BY 4.0 licence.
This review is written during the preparation of M‐era.Net full proposal  ʺGrain boundaries in multicomponent alloys without principal componentʺ (A.K., A.K., G.A.L.  and E.R., application No. 9345). The Institute of Solid State Physics, University of Latvia, as a cen‐ ter of excellence, has received funding from the European Union’s Horizon 2020 Framework Pro‐ gramme H2020‐WIDESPREAD‐01‐2016‐2017‐TeamingPhase2 under grant agreement no. 739508,  project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; titanium alloys; high‐entropy alloys; grain boundary wetting; phase transitions; phase diagrams